Optimal dispatch of regional electricity-thermal system with multi-energy storage based on source and load forecasting - XU Feng; TAO Yuanchao; LU Yi; QIU Peng; LI Xinyu; SUN Hao; QIN Hongpei (Zhejiang dianli, 2023)
With the continuous development of the new power system construction， the installed capacity of wind power， photovoltaic and other renewable energies has been further increased. The randomness and uncertainty of source and load bring great challenges to the operation of the power system. Therefore， an optimal dispatch method of energy storage in regional electricity-thermal system based on multi-energy source and load forecasting， which improves the accommodation level of photovoltaic by the flexible adjustment ability of multi-energy storage and electricity-thermal coupling characteristics of the system. Firstly， the photovoltaic output and electricity-thermal load are forecasted based on the improved extreme learning machine and K-means clustering algorithm. Then， the conditional value at risk is applied to quantize the impact of uncertainty of photovoltaic output on operation cost. With target of minimizing the weighting sum of operation cost and conditional value at risk， the optimized operation scheduling model of district electricity-thermal system， containing battery， flywheel energy storage and heat storage tank， is established. The regulation requirement for flexible operation of the electricity-thermal system can be achieved by multi-energy storage. Finally， the case study is conducted to demonstrate the effectiveness of the proposed method.